Association Between Environmental Smoke Exposure in Early Life and ADHD-like Behaviors in Chinese Preschoolers: Findings from Population Survey in Shenzhen - Yu-Liang Zhang; Wei-Kang Yang; Esben Strodl; Mao-Lin Zhang; Wei-Qing Chen (Toxics)
Environmental tobacco smoke (ETS) exposure is a public health concern linked to neurodevelopmental disorders like attention deficit hyperactivity disorder (ADHD). Prior studies link ETS to ADHD, but gaps remain regarding gender differences, critical exposure windows, and dose–response relationships. This study assessed ETS exposure’s association with ADHD-like behaviors in Chinese preschoolers, evaluating overall risk, critical periods, dose–response relationships, and gender differences. Analyzing data from 64,472 preschoolers, ETS exposure (prenatal; infancy, 0–1; and early childhood, 1–3 years) was assessed via parent questionnaires, and ADHD-like behaviors were measured using the Conners’ Parent Rating Scale-Revised, with associations examined via logistic regression. ETS-exposed children had a 49% higher ADHD-like behavior risk (AOR = 1.49, 95% CI: 1.38–1.62, p < 0.001), with dose–response effects: The risk increased from AOR = 1.25 (95% CI: 1.10–1.40) at low exposure to 2.24 (95% CI: 1.63–3.01) at high exposure. Prenatal (AOR = 1.42, 95% CI: 1.17–1.71) and infancy exposures (AOR = 1.43, 95% CI: 1.05–1.90) showed the strongest associations, while early childhood exposure (1–3 years) was non-significant (AOR = 1.04, 95% CI: 0.82–1.29). No gender-specific differences were observed. Early-life ETS exposure, particularly prenatally and in infancy, elevates ADHD-like behavior risk in preschoolers, demonstrating dose–response trends without gender disparity, highlighting the need for universal strategies to reduce such exposures.